(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Pyrazolyldiarylcyclohexenone derivatives have garnered significant attention in recent yearsdue to their potential biological activities and diverse pharmacological properties. In this study, wefocused on the synthesis and characterization of a series of novel pyrazolyldiarylcyclohexenonederivatives. The compounds were synthesized using well-established organic chemistry methods, andtheir structures were confirmed through various spectroscopic techniques such as NMR, IR, and massspectrometry. The biological evaluation of these derivatives was conducted through a range of in vitroand in vivo experiments. The assessment included studies on antimicrobial activity against variouspathogenic strains, antioxidant potential, anti-inflammatory effects, and cytotoxicity against cancer celllines. Additionally, we investigated their potential as enzyme inhibitors, which could offer therapeuticpossibilities for specific diseases.